Physiological and Pathophysiological Roles of Mitochondrial Na+-Ca2+ Exchanger, NCLX, in Hearts - Ayako Takeuchi; Satoshi Matsuoka (Biomolecules, 2021)
It has been over 10 years since SLC24A6/SLC8B1, coding the Na+/Ca2+/Li+ exchanger (NCLX), was identified as the gene responsible for mitochondrial Na+-Ca2+ exchange, a major Ca2+ efflux system in cardiac mitochondria. This molecular identification enabled us to determine structure–function relationships, as well as physiological/pathophysiological contributions, and our understandings have dramatically increased. In this review, we provide an overview of the recent achievements in relation to NCLX, focusing especially on its heart-specific characteristics, biophysical properties, and spatial distribution in cardiomyocytes, as well as in cardiac mitochondria. In addition, we discuss the roles of NCLX in cardiac functions under physiological and pathophysiological conditions—the generation of rhythmicity, the energy metabolism, the production of reactive oxygen species, and the opening of mitochondrial permeability transition pores.